Smart monitoring system for pressure regulator based on IOT - Aktham Hasan Ali; Ahmed Hussein Duhis; Nabeel Aad Lafta Alzurfi; Mohannad Jabbar Mnati (Institute of Advanced Engineering and Science, 2019)
In the last years, the interconnection of everyday instruments with internet using internet of thinks (IOT), is widely used as a monitoring and controlling in engineering as in smart cities, environmental, others. In this paper, a remote monitoring system of a pressure regulator is developed through an internet of thinks (IOT) communication tool, using MATLAB® programming platforms. The development of monitoring system for acquisition and communication corresponds to the NodeMCU as a microcontroller with ESP8266 for Wi-Fi connected. This system allows to monitor the reference of the pressure regulator and monitor the information of the transducers machine of the plant. Among the advantages of this type of development is that the server is free, and the development system is low cost, also with this type of projects can strengthen the infrastructure of laboratory equipment in engineering to be controlling in a way remote.